KUALITAS PELAYANAN TRANSJAKARTA BUSWAY DI DKI JAKARTA - Putri Yulfa Rianti; Retnowati WD Tuti (Universitas Muhammadiyah Jakarta, 2017)
This study discusses the Transjakarta Busway Ser- vice Quality In DKI Jakarta where in serving customers there are still obstacles that make customers feel satisfied to the service given. The purpose of this research is to know Transjakarta Busway Service Quality In DKI Jakarta. The theory used is according to Parasuraman (1990) in book Theory of Public Administration written by Harbani Pasolong (2014) with five indicators used to measure service quality that is: Reliability, Responsiveness, Assurance, Empathy, and Tangibel. The method used in this research is desscriptive method with kulaitatif approach. With the number of informants as many as 10 (ten) people determined by using purposive sampling technique 3 (Three) people and accidental sampling 7 (Seven) people. Data collection techniques used are observation, interview and documentation. In addition, data validity test using Triangulation method. Based on the result of the research shows that the Transjakarta Busway Service Quality In Jakarta is still not good, it can be seen from the five indicators used to bury the quality of Tranjakarta services that are Reliability, Responsiveness, Assurance, Empathy and Tangibel.Keywords: Quality, Service, Transjakata Busway